Improvement Model to Increase Productivity Using SLP, 5S and Standard Work at a Pisco Producer SME in Peru - Kcomt Villavicencio, Pedro Andre (2024)
Over the years, the Pisco industry has experienced a significant growth, which is why the SMEs in the sector need to improve their production processes. Many of these companies have difficulties in their production processes related to low productivity, mainly due to inefficient plant distribution. Therefore, the main purpose of this scientific article is to support these companies in the Pisco industry by increasing their productivity. This will be achieved by implementing the following improvement proposal using the engineering tools of Systematic Layout Planning, 5S and Standard Work. The proposal of this article is a new plant layout, in order to eliminate unnecessary transfers in the production process, alongside with standardized processes and an innovative temperature control system. The proposed model was validated with the use of Arena Software by comparing the pre-implementation and post-implementation results of the model, in order to verify if the implementation of these tools had a positive impact on the Pisco producing company. As a result, the productivity increased in 11%, the transfer times between stages were reduced from 20,36 hours to 13,86 hours, meaning a 31,92% reduction per production process; and the waste generated during the process were reduced by 11%. Also, from a financial point of view, a payback period of 1,51 years and a NPV of USD 3 938,92 were obtained.